FDTD Analysis with Overset Grid Generation Method for Rotating Body and Evaluation of Its Accuracy - Sahrani, S.; Kuroda, M. (IEICE TRANSACTIONS, 2013)
This paper presents an alternative approach for the analysis of EM field by a rotating body with FDTD method and Overset Grid Generation method, considering Lorentz transformation for the higher velocity cases. This approach has been previously proposed for the case of linear and uniformly moving body against/to the incident wave. Here, the approach is expanded to a rotating body which includes the interpolation technique in the space and time increment along the cylindrical rotation at the fixed axis. First, the grid size ratios between the main mesh and the sub-mesh are studied. The appropriate choice of the grid size ratio is obtained. Then, the modulations of the EM field when the incident wave hits the rotating body in high velocity cases are analyzed. The relationship of the phase shift and the velocity is further observed. The observed EM fields are compared with the theoretical results and achieved good agreements in high relative velocities. The assessment of the numerical errors in a rotating environment is also highlighted. This numerical approach may have numerous situations to which it can be applied. This may be involved with the design of rotating devices such as microactuator, commutator and others.